Effect of acute antidepressant administration on negative affective bias in depressed patients. - Harmer, C; O'Sullivan, U; Favaron, E; Massey-Chase, R; Ayres, R; Reinecke, A; Goodwin, G; Cowen, P (2009)
OBJECTIVE: Acute administration of an antidepressant increases positive affective processing in healthy volunteers, an effect that may be relevant to the therapeutic actions of these medications. The authors investigated whether this effect is apparent in depressed patients early in treatment, prior to changes in mood and symptoms. METHOD: In a double-blind, placebo-controlled, between-groups randomized design, the authors examined the effect of a single 4-mg dose of the norepinephrine reuptake inhibitor reboxetine on emotional processing. Thirty-three depressed patients were recruited through primary care clinics and the community and matched to 31 healthy comparison subjects. Three hours after dosing, participants were given a battery of emotional processing tasks comprising facial expression recognition, emotional categorization, and memory. Ratings of mood, anxiety, and side effects were also obtained before and after treatment. RESULTS: Depressed patients who received placebo showed reduced recognition of positive facial expressions, decreased speed in responding to positive self-relevant personality adjectives, and reduced memory for this positive information compared to healthy volunteers receiving placebo. However, this effect was reversed in patients who received a single dose of reboxetine, despite the absence of changes in subjective ratings of mood or anxiety. CONCLUSIONS: Antidepressant drug administration modulates emotional processing in depressed patients very early in treatment, before changes occur in mood and symptoms. This effect may ameliorate the negative biases in information processing that characterize mood and anxiety disorders. It also suggests a mechanism of action compatible with cognitive theories of depression.